Determinants of Dysfuntional Behaviour Among Auditors in Nigeria - Alexander DABOR (PT Keberlanjutan Strategis Indonesia, 2024)
Ensuring good audit quality has become germane in recent times following developments that have ridiculed the credibility of financial statements all over the world. Achieving a strong audit quality entails an auditor identifying and reporting pertinent abnormalities in corporate financial reports, demonstrating his expertise as a professional auditor. Audit quality remains fundamental in giving credibility to information presented in ?nancial statements. Reduced audit quality behavior remains a serious area of accounting and auditing literature and this can be ascribed to the importance of quality audits in a global business environment. This study is aimed at ascertaining the determinants of Dysfunctional audit behaviors. One hundred duplicates of organized questionnaires were given to selected accountants in the South-South region of Nigeria. This study employed a multivariate regression technique to analyze data collected from respondents. The results showed that auditor tenure and organizational commitment are inversely proportionate to dysfunctional behavior. The result further showed Task complexity and Time Budget Pressure are directly proportionate with dysfunctional behavior. This study recommended that commitment to audit should be tested periodically and should be used as the basis for retention. This study further recommended that elongated auditor tenure should be encouraged